Ahaetulla nasuta anomala (Annandale, 1906) (Squamata: Colubridae), resurrected as a valid species with marked sexual dichromatism - Mohapatra, Pratyush P.; Dutta, S. K.; Kar, Niladri B.; Das, Abhijit; Murthy, B. H. C.k; Deepak, V. (Zootaxa, 2017)
In this paper we resolve the taxonomic confusion related to Ahaetulla nasuta anomala (Annandale, 1906). On the basis of molecular and morphological data, we remove it from the synonymy of Ahaetulla nasuta (Lacépède, 1789) and reinstate it as a valid species—Ahaetulla anomala. This species is sexually dichromatic, males are green and females are brown in colour. Though the brown morph morphologically resembles Ahaetulla pulverulenta (Duméril, Bibron & Duméril, 1854) there are significant morphological and genetic differences between these two species. Additional information on taxonomy, natural history and distribution of the species is provided.